The Relationship Between Pornography Addiction and Cognitive Function in Young Adults in Banten - Aldo Valentino Thomas; Kevin Sulay Wijaya (Green Publisher Indonesia, 2026)
Physical and psycological changes that appear in teenager, and misused sexual information may lead to pornography contents usage, may cause addiction and compulsive behavior. There are 1809 pornography cases according to Survei Komnas Perlindungan Anak Indonesia from 2011 until 2016. Pornography interrupt working memory and attention, lead to cognitive disturbances. In Indonesia, there’re just a few of research study this topic. Research subjects also are just middle school students. So, researcher want to study it at young adult age. To understand the relationship between pornography addiction and cognitive at young adult in Banten On July to August 2018, this cross-sectional study was done, with 61 young adults in Banten. Data are gathered from online questionnaire. Excel 2010 and SPSS24 used for tabulation and data analysis, respectively.Significant results were obtained from relationship between pornography addiction and cognitive problem (p-value = 0.000; odds ratio [OR] 26.722; 95% confidence interval [CI95] 5.094 – 140.171). Gender significantly related with pornography addiction (p-value = 0.000; odds ratio [OR] 32.47; 95% confidence interval [CI95] 3.991 – 26.183), all samples with pornography addiction are men, men with pornography addiction (58%). Age don’t significantly related with pornography addiction (p-value: 0.158; odds ratio [OR] 0.313; 95% confidence interval [CI95] 0.034 – 2.853). Pornography duration don’t significantly related with pornography addiction (p-value: 0.293 [OR] 3.8; 95% confidence interval [CI95] 0.32 – 44.51), samples with excessive pornography duration more often have pornography addiction (67%) than samples with non excessive pornography duration (34%). Pornography addiction significantly related with cognitive impairment.